2011
DOI: 10.1177/0020764011423468
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the 2004 Asian tsunami: Epidemiological and nosological debates in the diagnosis of post-traumatic stress disorder in non-Western post-disaster communities

Abstract: Although PTSS were common in this population, elevating them to a psychiatric construct of PTSD is questionable, when functional impairment and avoidance behaviours were absent. Grief reactions, socio-economic burden, and poor support systems contribute towards PTSS. We highlight the important issues regarding the nosological validity and epidemiology of PTSD in non-Western communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 26 publications
(33 reference statements)
2
38
0
Order By: Relevance
“…Results of the current study corroborate a growing body of prior disaster mental health research, which found that post-disaster life stressors and traumas (Brewin et al, 2000; Cerda et al, 2012, in press; Kessler et al, 2012; Norris & Uhl, 1993; Norris et al, 2002a; Norris et al, 2002b; Tracy et al, 2011), including financial losses (Acierno et al, 2006; Galea et al, 2008; Rajkumar et al, 2011, in press; Su et al, 2010), are linked to severity, probable diagnoses, and chronicity of PTSD and related disorders. The finding that greater education was negatively related to a chronic symptom trajectory also accords with previous studies demonstrating the protective effect of this variable on risk for disaster-related PTSD and related mental disorders (Armenian et al, 2000; Norris et al, 2002a; Norris et al, 2002b; North et al, 2012; Yuan et al, 2012, in press).…”
Section: Discussionsupporting
confidence: 85%
“…Results of the current study corroborate a growing body of prior disaster mental health research, which found that post-disaster life stressors and traumas (Brewin et al, 2000; Cerda et al, 2012, in press; Kessler et al, 2012; Norris & Uhl, 1993; Norris et al, 2002a; Norris et al, 2002b; Tracy et al, 2011), including financial losses (Acierno et al, 2006; Galea et al, 2008; Rajkumar et al, 2011, in press; Su et al, 2010), are linked to severity, probable diagnoses, and chronicity of PTSD and related disorders. The finding that greater education was negatively related to a chronic symptom trajectory also accords with previous studies demonstrating the protective effect of this variable on risk for disaster-related PTSD and related mental disorders (Armenian et al, 2000; Norris et al, 2002a; Norris et al, 2002b; North et al, 2012; Yuan et al, 2012, in press).…”
Section: Discussionsupporting
confidence: 85%
“…It is important to consider that the concept of PTSD in non-Western populations with massive exposure to severe and ongoing trauma has been criticized (Rajkumar, et al, 2011; Summerfield, 2001). Without validating the diagnostic constructs under study, it may be possible that we have imposed a western conceptualization of distress on the local community that may not fully fit or missed mental health problems unique to this population (e.g., somatization).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to increase knowledge about the association between PTSD symptoms and functional impairment, because there is an ongoing debate on the controversial value of PTSD diagnosis and allocation of resources for trauma-focused care during and after acute emergencies, particularly in non-Western countries with massive exposure of the population to trauma (Rajkumar, Mohan, & Tharyan, 2011; Summerfield, 2001; Van Ommeren, Saxena, & Saraceno, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…However, elevating them to the construct of PTSD requires a minimum of three avoidance symptoms, two hyper-arousal symptoms, one re-experiencing symptom, and clinically significant distress or impairment in social, occupational, or other areas of functioning as per Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. [ 22 23 ] None of the participants with PTSS satisfied these criteria for PTSD, especially functional impairment. This study reports the presence of equal levels of PTSS in both boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of functional impairment, elevating them to a psychiatric diagnosis of PTSD is questionable. [ 23 ] The need to intervene to minimize the impact on children at the earliest, using simple psychosocial care by the available community resources, is important.…”
Section: Discussionmentioning
confidence: 99%